Penguatan Literasi Baca-Tulis Melalui Aktivitas Menulis Karangan Deskripsi Pada Siswa di Madrasah Ibtidaiyah (MI) Ash-Shidiq, Kabupaten Bandung - Devi, Lathifah Sandra; Hayati, Eti; Setiawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
Literacy Ability as an Important Early Foundation in Children's Lives. Literacy ability is an important early foundation in children's lives. Children socialize through language, and with their language skills, they are then able to ask questions and construct ideas to communicate to others. The Purpose of Strengthening Literacy. The purpose of strengthening literacy is to provide students with several important goals that have a positive impact on their development, both academically and personally. The Purpose of Students Writing Descriptive Essays The purpose of students writing descriptive essays is to develop their ability to describe or explain an object, place, event, or concept with high detail and clarity. The method of this activity is in the form of a descriptive essay writing activity carried out at the Madrasah Ibtidaiyah (MI) Ash-Shidiqiah School, Bandung Regency. The implementation of student descriptive writing goes through the following stages: Understanding the material of descriptive essays, Types of objects that can be described, Students are then given a theme to be developed into a writing about